0835 Sleep Habits, Parenting Style, And Anxiety In Children. (27th April 2018) - Paquet, C; Wilkerson, A; Calhoun, C; Walker, J; Kelly, C; Danielson, C
Abstract: Introduction: Sleep disturbances are reported at an average rate of 10 to 50 percent in school aged children and adolescents, depending on population and criteria for sleep problems. Adequate sleep quality and duration are especially important during these childhood years such as they are the setting for critical psychological and physiological development. Previous research has shown that children with sleep problems are more likely to have emotional and behavioral problems. A recent study has shown a significant relationship between sleep, parenting style, mood, and anxiety in late adolescence, but this relationship has yet to be explored in childhood. Methods: As part of a larger study, children ages 8–15 completed the Multidimensional Anxiety Scale for Children (MASC) and one question from the Sleep Habits Survey (SHS) that contains 15 items related to sleep disturbance common in children and adolescents. The child's caregiver completed the Alabama Parenting Questionnaire (APQ). Results: Twenty-three child-caregiver dyads have completed the measures thus far. Preliminary analyses show there were significant relationships between combined SHS score and the APQ inconsistent discipline subscale (p = .03). When looking at individual items on the SHS, one of the most frequently endorsed items was "had an extremely difficult time falling asleep, " a symptom of insomnia. This item was significantly correlated with MASC subscales generalized anxiety, human rejection, performance fear, and social anxiety (all ps < .05). Conclusion: This preliminary data indicates that a relationship between sleep, anxiety, and parenting style may exist early in childhood. These early findings indicate that sleep-focused interventions and education at the child and parent level could lend to successful prevention and treatment of anxiety disorders. More robust analyses, including incorporating a measure of depression, will be possible in the next five months as there will be 60–80 more dyads completing these measures for the parent study. Support (If Any): 5R01MH112209-02.